Przejawy agresywności współczesnej młodzieży i ich uwarunkowania rodzinne = Manifestations of aggressiveness of contemporary youth and their family determinants - Farnicka, Marzanna; Liberska, Hanna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper presents the results of research on family determinants of aggressive behaviours of the youth. The analysis included, among others, the adequacy of aggressive behaviours showed by the youth, the intensity of its hostility and the control over manifested aggressive reactions. The authors searched for the relations between manifestations of aggressiveness of the youth and the way they perceive parental attitudes.
Keywords: młodzież; zachowania agresywne; wrogość; postawy rodzicielskie; youth; aggressive behaviour; hostility; parental attitudes